Plasmopara viticola RxLR effector PvAvh77 triggers cell death and governs immunity responses in grapevine. (9th January 2023) - Fu, Qingqing; Wang, Yunlei; Yang, Jing; Jiao, Yu; Li, Wenjuan; Yang, Fan; Yin, Xiao; Shang, Boxing; Liu, Ruiqi; Zhang, Yiyuan; Saileke, Ayisuwake; Liu, Guotian; et al.
Abstract: Grapevine downy mildew, caused by the oomycete Plasmopara viticola, is one of the most significant production challenges for the grape and wine industry. P. viticola injects a plethora of effectors into its host cells to disrupt immune processes, but the mechanisms by which these effectors act at the molecular level have not been well characterized. Herein, we show that a candidate P. viticola avirulence homolog (Avh) RxLR effector gene, designated PvAvh77, was strongly up-regulated during the initial stages of P. viticola infection in Vitis vinifera . Further experiments demonstrated that PvAvh77 could trigger non-specific cell death when expressed in the wild grapevine Vitis riparia and in tobacco ( Nicotiana benthamiana and Nicotiana tabacum ). In addition, a truncated form of PvAvh77, designated PvAvh77-M2, was more active in inducing cell death in N. benthamiana and V. riparia than full-length PvAvh77. Ectopic expression of PvAvh77 in V. vinifera 'Thompson Seedless' leaves neutralized host immunity and enhanced colonization by P. viticola, and the immune-inhibiting activity of PvAvh77 on susceptible Eurasian grapevine depended on its nuclear localization. Using a yeast signal sequence trap approach, we showed that the signal peptide of PvAvh77 is functional in yeast. Moreover, PvAvh77 with a signal peptide stimulated plant immune responses in the apoplast. Notably, application of exogenous purified PvAvh77-M2 effectively initiated defence responses in grapevine extracellularly, as evidenced by increased accumulation of salicylic acid and H2 O2, and reduced infection of inoculated P. viticola . In summary, we identified a novel effector, PvAvh77, from P. viticola, which has the potential to serve as an inducer of plant immunity. Abstract : The Plasmopara viticola effector PvAvh77 induces cell death, suppresses plant immunity intracellularly, and triggers responses extracellularly.